2019
DOI: 10.1073/pnas.1910225116
|View full text |Cite
|
Sign up to set email alerts
|

Water follows polar and nonpolar protein surface domains

Abstract: The conformation of water around proteins is of paramount importance, as it determines protein interactions. Although the average water properties around the surface of proteins have been provided experimentally and computationally, protein surfaces are highly heterogeneous. Therefore, it is crucial to determine the correlations of water to the local distributions of polar and nonpolar protein surface domains to understand functions such as aggregation, mutations, and delivery. By using atomistic simulations, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
100
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 77 publications
(114 citation statements)
references
References 75 publications
(109 reference statements)
6
100
0
Order By: Relevance
“… 30 A simple estimate using a dielectric permittivity reduction from 80 to 8 up to ∼1 nm from the protein surface changes the Coulomb energy ( E ) over thermal energy ( k B T ) between two elementary charges ( e ) separated by a distance d [ E / k B T = e ( 2 )/(4 r d )/ k B T = l B / d ] from 0.7 to 7 when d = 1 nm, also strongly reducing the debye length from the value in water (∼1 nm in bulk water with 150 mM of NaCl). An increase in protein’s absolute net charge, which drives stronger interfacial correlations, 24 therefore, explains the long-range impact of the polybasic cleavage sites on the RBD–ACE2 binding given the fact that the SARS-CoV-2 spike protein trimer and ACE2 are both highly negatively charged with a net charge of −21 e and −28 e , respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 30 A simple estimate using a dielectric permittivity reduction from 80 to 8 up to ∼1 nm from the protein surface changes the Coulomb energy ( E ) over thermal energy ( k B T ) between two elementary charges ( e ) separated by a distance d [ E / k B T = e ( 2 )/(4 r d )/ k B T = l B / d ] from 0.7 to 7 when d = 1 nm, also strongly reducing the debye length from the value in water (∼1 nm in bulk water with 150 mM of NaCl). An increase in protein’s absolute net charge, which drives stronger interfacial correlations, 24 therefore, explains the long-range impact of the polybasic cleavage sites on the RBD–ACE2 binding given the fact that the SARS-CoV-2 spike protein trimer and ACE2 are both highly negatively charged with a net charge of −21 e and −28 e , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The hydrophobic leucine (Leu) residue was introduced to decrease the hydration, as a test simulation on a tetrapeptide EEEE showed that EEEE became quickly dissolved (within 10 ns) owing to the high hydration of the negatively charged amino acids. 24 26 …”
Section: Resultsmentioning
confidence: 99%
“…All the covalent bonds were constrained, which supported an integration time step of 2.5 fs. These parameters were recommended for the accurate reproduction of the original CHARMM simulation on lipid membrane system 38 and were verified in simulations on proteins 20,39,40 and lipid membranes 41 . The production simulation lasted 100 ns.…”
Section: Figure 4 Simulation Methods In the Absence (B-e) And Presencmentioning
confidence: 95%
“…Moreover, the substitution of positively charged arginine with negatively charged glutamic acid increases protein hydration (Table S2), which is consistent with the fact that negatively charged amino acids exhibit stronger hydration than positively charged ones. [20][21][22] Further analysis of the intermolecular hydrogen bonds between the RBD and ACE2 demonstrated a similar influence of the mutants (Figure 2F). For the WT spike protein, there exist 8 ± 1 hydrogen bonds between the RBD and ACE2.…”
Section: Demonstrated Inmentioning
confidence: 94%
See 1 more Smart Citation